Pengaruh Motivasi Dan Disiplin Kerja Terhadap Kinerja Karyawan Pada Restoran Domino’s Pizza Region Bekasi 2 Di Wilayah Jakarta Timur - Agung Nugraha, Adhitya; Andriani, Jeni (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
Abstrak. The objective of this research is to know partially and simultaneously the effect of motivation and work discipline on employee performance at Dominos’ Pizza Region Bekasi 2 Jakarta Timur. This research method is an associative study using a quantitative approach. The subjects of this study were all 74 employees of the Dominos’ Pizza Region Bekasi 2 Jakarta Timur. While the sample used was 74 respondents using saturated sample technique. Data collection using, questionnaires, documentation, and literature study. Meanwhile, the data analysis used validity test, reliability test, normality test, multicorrelation test, heteroscedasticity test, linear regression, determination coefficient, and significant test (t test and F test). Based on the results of the study, the tcount value for the Motivation Variable (X1) on Performance (Y) is 6,460 > 1,669. It can be concluded that the Motivation variable has a positive influence on performance. The tcount for the Work Discipline (X2) variable on performance (Y) is 2.020 > 1.669. It can be concluded that the Work Discipline variable has significant effect on performance. Obtained multiple linear regression equation model Y = 6,903+ 0,190 X1 + 0,689 X2. The Coeffcient Correlation (R) value is 0.629, which means the correlation of Motivation and Work Discipline on Employee Performance in the Strong category (0.60 – 0.799) with the coefficient of determination adjusted R2 (adjusted R Square) of 0.395. This shows that 39.5% of Employee Motivation and Work Discipline simultaneously (jointly) affect employee performance, while the remaining 60.5% is influenced by other factors not examined in this study Keywords: Motivation, Work Discipline, Employee Performance